Pengaruh ROE dan DER Terhadap Dividend Payout Ratio pada Industri Barang Konsumsi di Bursa Efek Indonesia - Wiwin Roslinda Sidebang; Ade Ali Nurdin; Mochamad Edman Syarief (Indonesian Journal of Economics and Management, 2022)
This research was conducted the Financial Statements of the Consumer Goods Industry listed on Bursa Efek IndonesiaIn 2014-2019. The phenomenon occurs is the consumer goods industry experiences fluctuating amount of net profit so Return On Equity (ROE) is the same. Most of the capital cannot meet the amount of debt, which makes the value of Debt to Equity Ratio (DER) high. In addition, companies continue to provide dividends even though experience losses. The purpose of this was to determine effect of ROE and DER on Dividend Payout Ratio (DPR). Using Panel Data Regression Analysis through three approach models, namely common effect, fixed effect and random effect. Chow test, Hausman test and Langrangian multiplier test were carried out to find appropriate approach. The result is that ROE and DER simultaneously have a significant effect on DPR. Furthermore, partially ROE and DER have an effect on DPR.